Lack of ADAM10 in endothelial cells affects osteoclasts at the chondro‐osseus junction. Issue 2 (21st September 2013) - Zhao, Ren; Wang, Aimin; Hall, Katherine C.; Otero, Miguel; Weskamp, Gisela; Zhao, Baohong; Hill, Daniel; Goldring, Mary B.; Glomski, Krzysztof; Blobel, Carl P.
Abstract Mice lacking ADAM10 in endothelial cells (Adam10ΔEC mice) have shorter femurs, tibiae, and humeri than controls, raising questions about how endothelial cells could control long bone growth. We performed a histopathological evaluation of the femur and tibia growth plates at different postnatal stages, and assessed the distribution of TRAP‐positive osteoclasts and endothelial cells at the growth plate. The growth plates in Adam10ΔEC mice appeared normal at P7 and P14, but a thickened zone of hypertrophic chondrocytes and increased trabecular bone density were apparent by P21 and later. The number of TRAP+ cells at the COJ was normal at P7 and P14, but was strongly reduced at P21 and later. Moreover, the density of endomucin‐stained endothelial cells at the COJ was increased starting at P7. The defects in long bone growth in Adam10ΔEC mice could be caused by a lack of osteoclastogenesis at the COJ. Moreover, ADAM10 appears to regulate endothelial cell organization in the developing bone vasculature, perhaps in a similar manner as in the developing retinal vascular tree, where ADAM10 is thought to control Notch‐dependent endothelial cell fate decisions. This study provides evidence for the regulation of osteoclast function by endothelial cells in vivo. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:224–230, 2014.